C-Reactive Protein in Patients with NSTEMI Acute Coronary Syndrome - Dubey, RK; Dhakal, N; Das, BKL; Pandey, NK; Baral, N; Lamsal, M (Journal of Universal College of Medical Sciences, 2013)
Background: C- reactive protein (CRP) is an acute phase inflammatory mediator that has been implicated as a risk factor for cardiovascular disease (CVD). The clinical presentation of acute coronary syndrome (ACS) ranges from unstable angina (UA) to non ST- segment elevation myocardial infarction (NSTEMI) and ST- segment elevation myocardial infarction (STEMI). Although, elevated levels of serum CRP have been reported in patients with CVD, the serum levels of CRP in patients with NSTEMI ACS is unknown. The purpose of the study was to determine whether the serum levels of CRP are higher in patients with NSTEMI ACS as compared to healthy controls. Methods: The study subjects consisted of two groups. Group I: (controls) twenty- five age-matched healthy men and Group II: Forty- five NSTEMI ACS patients. Fasting blood samples were collected and serum levels of CRP were measured by using highly sensitivity immunoassay rate method technology. Results: The serum levels of CRP in Group I and Group II were 3.2 ± 0.25 and 11.32 ± 2.1 mg/L, respectively and these values were significantly different from each other (p< 0.05). Group II showed a 253% higher level of CRP as compared to Group I subjects. Conclusion: The results demonstrate that the serum levels of CRP are higher in patients with NSTEMI ACS as compared to controls. Serum CRP levels are elevated in patients with NSTEMI ACS and may contribute to the inflammation and thrombosis associated with acute coronary syndrome. DOI: http://dx.doi.org/10.3126/jucms.v1i1.8416 Journal of Universal College of Medical Sciences Vol.1(1) 2013: 10-14